2021
DOI: 10.3390/nano11010106
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of Viscoelastic Behaviors of Nano-TiO2/CaCO3 Modified Asphalt and Asphalt Mixture

Abstract: The purpose of this paper is to promote the application of nano-TiO2/CaCO3 in bituminous materials and present an experimental characterization of viscoelastic behaviors of bitumen and bituminous mixture modified by nano-TiO2/CaCO3. In this work, a series of viscoelastic behavior characterization tests were conducted, including dynamic shear rheometer (DSR) test for bitumen, uniaxial static compression creep test and dynamic modulus test for bituminous mixture. Moreover, various viscoelastic models with clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Two commonly used viscoelastic models, i.e., the Burgers model and modified Burgers model, are adopted to fit the above-measured creep deformation curves. The Burgers model and modified Burgers model have been described in detail in previous studies [ 34 , 40 , 41 ], and are given in Equations (1) and (2). where E 1 , E 2 , η 1 , and η 2 are viscoelastic parameters, and A and B are fitting constants.…”
Section: Resultsmentioning
confidence: 99%
“…Two commonly used viscoelastic models, i.e., the Burgers model and modified Burgers model, are adopted to fit the above-measured creep deformation curves. The Burgers model and modified Burgers model have been described in detail in previous studies [ 34 , 40 , 41 ], and are given in Equations (1) and (2). where E 1 , E 2 , η 1 , and η 2 are viscoelastic parameters, and A and B are fitting constants.…”
Section: Resultsmentioning
confidence: 99%
“…To further quantitatively analyze the influence of temperature on creep characteristics of OGFC, the Burgers model and modified Burgers model, shown in Figure 3 and Equations ( 17) and (18), were applied to fit the creep compliance curve [30][31][32][33]. The parameters of the two models are fitted by the programming algorithm in Excel software (Microsoft Corporation, Albuquerque, NM, USA) according to Equation (19).…”
Section: Creep Characteristic Analysis Based On the Burgers Model And The Modified Burgers Modelmentioning
confidence: 99%
“…Many researchers around the world tried to use different methods to enhance the service performances of asphalt pavement, and many additives like polymers, diatomite, fibres, etc. were selected to mix with asphalt materials [9][10][11][12][13]. Studies demonstrated that diatomite has been effective in improving the anti-rutting performance and water damage resistance [14].…”
Section: Introductionmentioning
confidence: 99%